Assistance in implementing Islamic Business Principles at Nomadix Cafe - Dewi, Azizah Putri; Abidin, Zaenal; Wandi, Wandi; Haeran, Haeran (CV. Zabags Qu Publish, 2024)
This research aims to assist Nomadix Cafe in implementing Islamic business principles which include honesty, justice, and social responsibility. The methodology used is a qualitative approach with a case study method, which involves observation, in-depth interviews, and focus group discussions (FGD) with management and employees. In addition, periodic assistance and evaluation processes are carried out to support the understanding and application of these principles. The results of the study show that the application of Islamic business principles at Nomadix Cafe increases customer trust, employee loyalty, and overall business image. However, obstacles in Islamic financial management are still found. Based on these results, it is recommended that Nomadix Cafe and similar businesses deepen their understanding of Islamic finance principles, continue periodic evaluations, and actively involve management to ensure that the application of Islamic principles runs consistently and supports business sustainability